EMPOWERMENT OF LIVESTOCK AT PURE FRESH DAIRY FARM THROUGH SOCIALIZATION AND GOAT MILK YOGURT PRODUCTION - Wijayanti, Dwi; Hikmatyar, Missi; Rahwana, Kusuma Agdhi; Fadillah, Muhammad Gustyar; Nugraha, Erin Fajrin; Kasyfurrahman, Muhammad Akbar; Sacadiraksa, Widia Fajrin (LPPM Univ. Ibn Khaldun Bogor, 2024)
This service aims to enhance the quality and quantity of the breeding farm at Pure Fresh Dairy Farm by diversifying dairy products, specifically goat milk yogurt, and promoting them through e-commerce branding and marketing. The method used is participatory action research, where the implementation team and partners together, assisted by students, jointly carry out community service activities from socialization, training, and mentoring as well as socialization in making goat milk yogurt and product marketing. The service results revealed that the farmer's knowledge was only 25% before the socialization and training, but after these activities, the farmer's understanding increased to 100%. The results of the yogurt organoleptic test showed a pure white color, a soft texture, a not-too-pungent aroma, a sour taste, and medium viscosity. The goat milk yogurt is branded as 'Pure Fresh Dairy for Happiness Goat Milk Yoghurt'. We engage in marketing by setting up accounts on Instagram and Shopee platforms. The impact of this service is to provide knowledge to farmers, particularly Pure Fresh Dairy Farm partners, about the technology of diversifying dairy products in the form of yogurt and to add value to their income through the sale of goat milk yogurt products.